Exact null controllability of semilinear evolution systems - Mahmudov, Nazim I. (Springer, 2013)
We study the exact null controllability for the abstract evolution equations in Hilbert spaces. Assuming the exact null controllability of the corresponding linearized equation we obtain sufficient conditions for the exact null controllability of the semilinear evolution equation. The results we obtained are generalization and continuation of the recent results on this issue. In the end, an example is given to show the application of our result.
Keywords: Exact null controllability; Evolution equations; Fixed point